Strategies for national and local development: A public management proposal with an ethical approach - Pinedo López, Jhon William; Lora Ochoa, Carmen; Torres Hoyos, Francisco José (Cooperativismo & Desarrollo, 2021)
The central purpose of this work is to present a proposal for local and national development strategies, aimed at contribute to the improvement of the adverse social, economic and environmental indicators presented in the Colombian context. The methodology is purposeful as part of a diagnosis of local, national, social, economic and environmental situation that allows the design of the proposal with an emphasis on ethics, based on the principles of truth, justice, kindness, cooperation, solidarity and responsibility. The Main results is that local, and national development plans are not enough to reduce the negative statistics in terms of coexistence, economy and sustainability and to contain crime, in that way, they allow Governments to achieve goals. One important conclusion is that, this proposal is a viable option, since it contains the fundamental principles to achieve a sustainable society despite the differences of human beings and because it is designed to reach all social sectors and contribute to renewing the individual way of thinking and the collective imagination that rejects the principles mentioned in the 21st century.
Keywords: strategies; solidarity; development; economy; sustainability